THE ARTICULATION OF THE NOTES IN TREATIES DEDICATED TO WOODWIND INSTRUMENTS FROM THE BAROQUE ERA - Ignác Csaba FILIP (Studia Universitatis Babeş-Bolyai. Musica)
The articulations described in the treaties from the baroque era give proof to a wider variety, compared to the ones used in our days. The knowledge and application of these types of articulations offers a possibility to spread and enrich the expression palette of each performer and can be used not only with baroque instruments but also by performers of modern instruments.